Local Enterprise Partnerships: Seven-year itch, or in need of a radical re-think? – Lessons from Cambridgeshire and Peterborough, UK. (March 2019) - Marlow, David
England has struggled to create and sustain intermediate tier institutions of leadership and governance between national government (UKG) and local authorities. This 'in perspective' paper reflects on the establishment of 39 Local Enterprise Partnerships between 2010 and 2012, and their assumption of increasing powers and resources during their first seven years of existence (2010–17). This is considered in the light of the lessons of the Greater Cambridgeshire Greater Peterborough Local Enterprise Partnership. Greater Cambridgeshire Greater Peterborough Local Enterprise Partnership was a first round Local Enterprise Partnerships eventually wound up and absorbed into a Mayoral Combined Authority – itself a new form of intermediate tier institution – in early 2018. Greater Cambridgeshire Greater Peterborough Local Enterprise Partnership exemplifies the challenges of intermediate tier leadership and governance in England in many ways – the tensions between administrative and functional economic geographies; between national and local legitimacy and accountabilities; between political, business, and third sector stakeholders; between strategic leadership and delivery effectiveness. In mid-2018 Government's 'Strengthened LEPs' Review – partly stimulated by the Greater Cambridgeshire Greater Peterborough Local Enterprise Partnership experience – sought to reconcile some of these tensions. The paper suggests major limitations with the review's approach, which may also have surfaced fundamental contradictions in Government's devolution ambitions and policies. England will almost certainly need a new approach to local and regional growth as BREXIT issues play out over 2019–21, and as it seeks to deliver Local Industrial Strategies. The Local Industrial Strategies seek to tackle fundamental industrial and inclusive growth challenges across England's cities and regions with their wide territorial variations in performance. Whether this can be founded on an evolution of the Local Enterprise Partnership system or requires a radical fresh start remains an open question.